To what extent is personality associated with time perspective? - Muro, Anna; Castellà, Judit; Sotoca, Cristina; Estaún, Santiago; Valero, Sergi; Gomà-i-Freixanet, Montserrat (Anales de Psicología / Annals of Psychology, 2015)
Recent research has focused on behavioral correlates of temporal perspective (TP), suggesting that this individual difference has an influence on many health-related behaviors such as smoking and substance use, physical activity or life satisfaction. It is suggested that a consistently biased temporal orientation is associated with some psychiatric disorders and mediated by personality factors. However, few studies have explored the relationship between personality and TP from a psychobiological approach. The aim of the study was to examine the relationship between the Zimbardo Time Perspective Inventory (ZTPI) and Zuckerman-Kuhlman Personality Questionnaire (ZKPQ) in a sample of 196 undergraduate students through a multiple regression analyses. Results showed that: Past-Negative correlated positively with Neuroticism-Anxiety and negatively with Activity; Present Hedonistic correlated positively with Impulsive-Sensation Seeking and Sociability in a very high degree; and Future correlated positively with Neuroticism-Anxiety and Activity, and negatively with Impulsive-Sensation Seeking. Results are discussed in terms of the definition of both scales, their relationships and their implications in applied fields.